Genetic variability for yield and nutritional quality in yam bean (Pachyrhizus sp.) - Agaba, R.; Tukamuhabwe, Phineas; Rubaihayo, P.R.; Tumwegamire, Silver; Ssenyonjo, A.; Mwanga, Robert O.M.; Ndirigwe, J.; Grüneberg, W.J. (American Society for Horticultural Science, 2016)
The amount of genotypic and phenotypic variability that exists in a species is important for selection and initiating breeding programs. Yam bean is grown locally in tropical countries of the Americas and Asia for their tasty storage roots, which usually have low dry matter content. The crop was recently introduced in Uganda and other East and Central African countries to supplement iron (Fe) and protein content in diets. This study aimed to estimate genetic variability for root yield and quality traits among 26 yam bean accessions in Uganda. A randomized complete block design was used with two replications across two ecogeographical locations and two seasons during 2012 and 2013. Near-infrared reflectance spectroscopy (NIRS) was used to determine quality of storage root samples. Significant differences among genotypes were observed for all traits except root protein, zinc (Zn), and phosphorus contents. Genotypic variance components (s2 G) were significant for storage root fresh yield (SRFY), storage root dry matter (SRDM), storage root dry yield (SRDY), vine yield (VNY), fresh biomass yield (FBY), and storage root starch (STA) and Fe contents. For traits with significant s2 G; the broad sense heritability estimates ranged from 58.4% for SRDY to 83.6% for FBY; and phenotypic coefficients of variation were high for SRFY (66%), SRDY (53.3%), VNY (60.5%), and FBY (59%), but low to medium for SRDM (22.6%), STA (15.1%), and Fe (21.3%). Similarly, the genotypic coefficients of variation were high for SRFY (56.7%), SRDY (53.3%), VNY (55%), and FBY (53.9%); and low for SRDM (20%), STA (12.4%), and Fe (17.8%). There were strong positive correlations between SRFY and both SRDY (r = 0.926) and FBY (r = 0.962), but low-to-moderate correlations among quality traits. It should be possible to breed for high dry matter yam beans by using low dry matter accessions due to the observed genetic variation (s2 G = 9.3%2), which is important if the high dry matter Pachyrhizus tuberosus accessions (known as chuin) from Peru cannot be accessed. This study indicated substantial genetic variation for yield and quality traits in yam bean, demonstrating potential for adaptability to growing conditions and consumer needs in East and Central Africa and for genetic improvement through selection.